Red electroluminescent devices based on rubrene derivative in 4,4′- N, N′-dicarubreneazole-biphenyl host and its application in white light emitting device for lighting purpose - Li, Tianle; Li, Wenlian; Li, Xiao; Han, Liangliang; Chu, Bei; Li, Mingtao; Hu, Zhizhi; Zhang, Zhiqiang (Solid-state electronics, 2009)
A rubrene (Ru) derivative, 2-formyl-5,6,11,12-tetraphenylnaphthacene (2FRu) was synthesized and was used as red dopant in N, N′-bis-(1-naphthyl)- N, N′-diphenyl-1,1′-biphenyl-4,4′-diamine (NPB) host in organic light-emitting device (OLED) that offers an emission peak at ∼598 nm and a current efficiency of 2.12 cd/A. The red emitter was also used to fabricate a white OLED (WOLED), in which 2FRu, tris-(8-hydroxyquinoline) aluminum (Alq 3) and NPB contribute to the red, green and blue emissive components, respectively. As a result, a high color rendering index of 89.8, CIE coordinates of (0.33, 0.33) at 11 V as well as a maximum luminance of 5000 cd/m 2 and a luminance efficiency of 4.72 cd/A were obtained. The performances suggest its potential applications for solid-state lighting. Also, the design and electroluminescent processes of the WOLED based on 2FRu were also discussed.